Pengaruh Pemberian Senam Yoga Terhadap Penurunan Skor Stres Pada Mahasiswi Magister Keperawatan Di Universitas Gadjah Mada - Muhshanah; Ibrahim Rahmat; Intansari Nurjannah (PT. Hasba Edukasi Mandiri, 2025)
The Effect of Yoga Gymnastics on Reducing Stress Scores in Master of Nursing Students at Gadjah Mada University. Stress can occur in every individual including students. Stress can cause negative impacts, namely psychological and physical impacts. Aims: This study aims to determine whether yoga exercises can reduce stress levels in Master of Nursing students at Gadjah Mada University. Method: Research design using Quasi experimental with pretest-posttest research design with control group design. Sampling using purposive sampling. There were 60 respondents who were divided into 2 groups, namely 30 respondents as the intervention group and 30 respondents as the control group. The instrument used in this study was the Perceived Stress Scale 10 (PSS-10). Bivariate analysis using Independent T-test, Paired Sample T Test and Saphiro-Wilk test. Results: The stress score before the intervention group was 25.5 and after the intervention decreased to 12.9 with a significance of p=0.00 (p<0.05). The average stress score in the control group before was 23.9. The average stress score in the control group after was 24.5 with a significance value of p=0.05. The intervention group stress decreased by 12.6 while the control group stress score increased by 0.6 with p value <0.05. Conclusion: Giving yoga exercises has a significant effect on reducing the stress level of nursing magaister students at Gadjah Mada University.